ประสิทธิผลของโปรแกรมปรับเปลี่ยนพฤติกรรมการรับประทานอาหาร โดยประยุกต์ทฤษฎีขั้นตอนการเปลี่ยนแปลง ในประชากรกลุ่มเสี่ยงโรคเบาหวาน ชนิดที่ 2 - เรืองสิริวัฒก์, ณิชาพัฒน์; พิชยภิญโญ, ปาหนัน; ละกำปั่น, สุนีย์ (Journal of Public Health Nursing, 2016)
การวิจัยกึ่งทดลองครั้งนี้มีวัตถุประสงค์เพื่อศึกษาประสิทธิผลของโปรแกรมปรับเปลี่ยนพฤติกรรมการรับประทานอาหารโดยประยุกต์ทฤษฎีขั้นตอนการเปลี่ยนแปลงในกลุ่มเสี่ยงโรคเบาหวาน ชนิดที่ 2 ที่อาศัยอยู่ที่ตำบลคอกกระบือ จังหวัดสมุทรสาคร ทำการสุ่มกลุ่มตัวอย่างจำนวน 76 คนโดยแบ่งเป็นกลุ่มทดลอง (38 คน) และกลุ่มเปรียบเทียบ ( 38 คน) เกณฑ์การคัดเข้าการวิจัย ได้แก่ ประชากรที่มีอายุระหว่าง 35-59 ปี ไม่มีประวัติเป็นโรคเบาหวานและมีปัจจัยเสี่ยงการเกิดโรคเบาหวาน กลุ่มทดลองได้รับแผ่นพับฉลาดเลือกบริโภคป้องกันโรคเบาหวานและเข้าร่วมกิจกรรมซึ่งประกอบด้วย การวิเคราะห์พฤติกรรมตนเอง ดูตัวแบบด้านบวก สาธิตการฝึกตวงและฝึกการบันทึกอาหาร ในขณะที่กลุ่มเปรียบเทียบได้รับเพียงแผ่นพับ การเก็บรวบรวมข้อมูลใช้แบบสอบถามที่ระยะก่อนการทดลอง หลังการทดลองสัปดาห์ที่ 5 และ 8 ข้อมูลถูกวิเคราะห์ด้วยสถิติเชิงพรรณา chi-square Independent t-test และ Repeated measure ANOVA ผลการวิจัยพบว่า กลุ่มทดลองมีคะแนนเฉลี่ยความตระหนักในการรับประทานอาหาร ความสมดุลในการตัดสินใจ การรับรู้ความสามารถของตนเองและพฤติกรรมการรับประทานอาหารป้องกันโรคเบาหวานในสัปดาห์ที่ 5 และ 8 สูงกว่าก่อนการทดลองและกลุ่มเปรียบเทียบ อย่างมีนัยสำคัญทางสถิติ (p-value < 0.05) และพฤติกรรมส่วนใหญ่ของกลุ่มทดลองอยู่ในขั้นปฏิบัติ ข้อเสนอแนะจากผลการวิจัย คือ ก่อนการจัดกิจกรรมให้บุคคลควรมีการประเมินความพร้อมในการปรับเปลี่ยนพฤติกรรมและกิจกรรมที่ให้ควรเหมาะกับขั้นตอนที่ประเมินได้ในขณะนั้น AN EFFECTIVENESS OF PROGRAM APPLYING THE TRANSTHEORETICAL MODEL IN DIETARY CONSUMPTION AMONG POPULATION AT RISK OF DIABETES MELLITUS TYPE 2 The purpose of this quasi-experimental research was to investigate the effectiveness of dietary consumption behaviors by applying the Transtheoretical Model among a population at risk for Diabetes Mellitus type 2 residing in Khok Krabue Tambon. Samutsakorn province. A total of 76 subjects were randomly selected into the experimental group (n=38) and the comparison group (n=38). The inclusion criteria were those who aged 35-59 years old, no history of DM type 2, and were at risk 0f DM type 2. The experimental group received a dietary consumption leaflet for DM prevention developed by Ministry of Public Health, and participated in activities including analysis of own dietary consumption, positive role models discussion, food portion demonstrations and practice, and daily monitor practice, whereas the comparison group received only the leaflet. Data were collected by self-administered questionnaires at the beginning, the 5thweek, and the 8th week. Statistical analysis was performed using Descriptive statistics, Chi-square test, Independent t-test, and Repeated measure ANOVA. The results revealed that at the 5thweek and the 8thweek, the experimental group had a significantly higher mean score of awareness, decisional balance, perceived self-efficacy, and dietary consumption behaviors than those at the baseline and the comparison group (p-value < .05). The experimental group was mostly in the stage of action. Recommendations are that ready to change should be assessed at the early stage of program and activities should be tailored to people’s needs at their particular point in the change process.